PENINGKATAN KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK MELALUI OPEN ENDED PROBLEM - Naili Luma'ati Noor (Sekolah Tinggi Agama Islam Negeri (STAIN) Kudus, 2020)
Mathematical communication skills which include the ability to write, draw, and express mathematics are an important part of learning mathematics. Teachers need to design learning to develop mathematical communication skills. Open-ended problems allow students to convey their ideas and concepts which is the initial part of developing mathematical communication skills. The purpose of this study was to test the improvement of mathematical communication skills through habituation of open-ended problems on the material wide plane shapes. This type of research is experimental with a quasi-experimental design method. Data obtained through tests of mathematical communication skills before and after refraction open-ended questions on the material wide flat area. Data analysis using paired t-test and continued with the normalized gain test. The results showed there was an increase in mathematical communication skills with <g>=0,42 meaning an increase in mathematical communication skills in the medium category. Kemampuan komunikasi matematis yang meliputi kemampuan menulis, menggambar, dan mengekspresikan matematika merupakan bagian penting dalam pembelajaran matematika. Guru perlu mendesain pembelajaran untuk mengembangakan kemampuan komunikasi matematis.  Soal open ended memberikan kesempatan peserta didik untuk menyampaikan ide dan konsepnya yang menjadi bagian awal mengembangkan kemampuan komunikasi matematis. Tujuan penelitian ini untuk menguji peningkatan kemampuan komunikasi matematis melalui pembiasaan soal open ended  pada materi luas bangun datar. Jenis penelitian ini adalah eksperimen dengan metode quasi-experimental designs. Data diperoleh melalui tes kemampuan komunikasi matematis sebelum dan sesudah pembiasan soal open ended pada materi luas bangun datar. Analisis data menggunakan uji t berpasangan dan dialnjutkan dengan uji gain ternormalisasi. Hasil penelitian diperoleh terdapat peningkatan kemampuan komunikasi matematis dengan 〈g〉=0,42 artinya peningkatan kemampuan komunikasi matematis pada kategori sedang.